(3GdePeI aj GSJYeGd Cgd GdPeIs - (3eMeO Hf Ydj Hf YHO GdhGMO GdoqOnqcGdj Ke GdeUQj, CHh CeGeI, hjbGd dg GHf GdfbGT,J (B763 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI(B: (3SFd GdTjN GdEeGe GdYdGeI eaJi GdeSdejf TeS GdOjf CHh CeGeI Ydi GdTgjQ HEHf GdfbGT s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B25s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B96 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B241 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs